A preliminary assessment of carbon storage suitability in deep underground geological formations of New Brunswick, Canada - Keighley, Dave; Maher, Crystal (Atlantic Geoscience, 2015)
An assessment of the surface and subsurface geology in New Brunswick has identified several regions, close to Large Final Emitters (industrial sites releasing carbon dioxide, CO2, into the atmosphere), underlain by large volumes of various sedimentary rocks that could act as either the reservoir or seal in a carbon storage operation. There is a lack of subsurface data with which to make an assessment for the New Brunswick Platform, the Gulf of St. Lawrence, and Northumberland Strait. In the Moncton Basin, the McCully Gas Field is hosted in tight gas sands where it would be difficult to pump down CO2 at an economical rate. The Stoney Creek Oil and Gas Field south of Moncton is not at sufficient depth for CO2 to be in a supercritical state, necessary for compressed storage. Saline reservoirs could underlie suitably large areas around these fields, but again there is limited information on the quality of the potential reservoir rock. In the Bay of Fundy, south of Saint John, one borehole indicates a prospective location that includes a saline reservoir with suitable thickness and wireline-calculated porosity and permeability, a seal with suitable thickness, and limited faulting to potentially compartmentalize the reservoir or, conversely, compromise the continuity of the seal. The major uncertainty is trap volume, which is particularly difficult to assess based on the borehole being the only data point within a 50 km radius. This is also an environmentally sensitive offshore area. Until data deficiencies are addressed, no locations can be recommended for carbon storage.